Validation of the Technological Training Model for Primary School Teachers Using Structural Equation Modeling - Shamsi Gooshki, Sedigheh; Kamyabi, Mitra; Soltani, Amanallah; Manzari Tavakoli, Alireza (Assessment and Practice in Educational Sciences, 2026)
This study was conducted with the aim of designing and validating a technological training model for primary school teachers. In today's world, technological transformations have led to fundamental changes in educational structures, highlighting the need to prepare teachers equipped with technology-oriented competencies. Given the lack of comprehensive frameworks in this field, the study focused on identifying 13 key components, including critical and creative thinking, innovative problem solving, ethical responsibility, digital self-awareness, technological knowledge transfer, creation of technology-enhanced learning environments, interaction with technology for social and individual purposes, digital collaboration, mastery of modern tools, technological solution design, application of technology across diverse contexts, awareness of technological change trends, and appropriate technology assessment. The research method was quantitative and descriptive. The statistical population consisted of 850 primary school teachers and educational experts in Kerman Province, and the sample size was determined to be 265 using Cochran’s formula. Data were collected through a researcher-developed questionnaire based on a Likert scale. Construct validity was confirmed with RMSEA = 0.063 and CMIN/df = 2.34, and reliability was calculated using Cronbach’s alpha (0.74). Data analysis was performed using AMOS software. The results showed that the factor loadings of the components ranged from 0.48 to 0.74, and the t-values were significant (p < .001), indicating strong relationships between the components and the main construct of technological training. The model fit indices (CMIN/df = 2.34 and RMSEA = 0.063) confirmed the high validity of the proposed framework. This three-level model, integrating psychological, pedagogical, and technical dimensions, offers a more comprehensive structure than previous studies and can serve as a basis for educational policymaking, improving teaching quality, and preparing teachers for the digital age. It is recommended that this framework be incorporated into Iran’s curriculum programs to reduce challenges related to technology integration.